One-pot three-component synthesis and photophysical characteristics of novel triene merocyanines - Muschelknautz, Christian; Visse, Robin; Nordmann, Jan; Müller, Thomas J. J. (Beilstein Journal of Organic Chemistry, 2014)
Novel triene merocyanines, i.e. 1-styryleth-2-enylidene and 4-(1,3,3-trimethylindolin-2-ylidene)but-2-en-1-ylideneindolones are obtained in good to excellent yields in a consecutive three-component insertion Sonogashira coupling–addition sequence. The selectivity of either series is remarkable and has its origin in the stepwise character of the terminal addition step as shown by extensive computations on the DFT level. All merocyanines display intense absorption bands in solution and the film spectra indicate J-aggregation. While 1-styryleth-2-enylideneindolones show an intense deep red emission in films, 4-(1,3,3-trimethylindolin-2-ylidene)but-2-en-1-ylideneindolones are essentially nonemissive in films or in the solid state. TD-DFT computations rationalize the charge-transfer nature of the characteristic broad long-wavelength absorptions bands.
Keywords: alkynes; cross coupling; enamines; fluorescence; heterocycles; multicomponent reactions